HUBUNGAN ANTARA AKTIVITAS DALAM BERMAIN ESTAFET BOLA DENGAN KECERDASAN KINESTETIK ANAK - Oktaviah Amaliah; Tuti Hayati; Arif Nursihah (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
This research is based on the idea that play activities are a necessity for children. Playing ball relay is a game that affects various factors including kinesthetic intelligence, because this game uses gestures. This research was motivated by the gap between the high activity of playing ball relay and the low kinesthetic intelligence. It can be seen from the response of children who like to follow the game and the child's ability is still not optimal in processing the body simultaneously. This study aims to determine: (1) Children's activities in playing ball relay; (2) Early childhood kinesthetic intelligence; and (3) The relationship between children's activities in playing ball relay with kinesthetic intelligence in group B RA Al-Hasanah, Bandung Regency. This study used quantitative correlation method, the subjects used were 22 people consisting of 12 men and 10 women, data collection techniques using observation. The results obtained by playing ball relay with an average score of 77 are well interpreted while kinesthetic intelligence with an average score of 75 is also well interpreted. Furthermore, the relationship between activity in ball relay play and early childhood kinesthetic intelligence obtained a correlation coefficient of 0.51 moderate correlation. In addition, there is a 26% contribution made by football relay activities to kinesthetic intelligence.